A Study on Dynamics of Major Cereal Crop Production in Nepal - Dahal, Niroj; Ghimire, Sarthak; Poudel, Rakshya (International Journal of Social Sciences and Management, 2022)
Paddy, maize and wheat occupy the maximum share in terms of area and production of Nepalese agriculture and plays major role in food and nutrition security in Nepal. Although government has been investing in cereal production since 1960s and there is a slow and steady growth in area, production and yield. In this scenario, there is dearth of research studies which provides overview of the growth and instability of the cereal crops, and it is also necessary to identify the causes of the growth in production. This paper tries to address the fore mentioned issue by measuring the growth rate and instability in area, production and yield of paddy, wheat and maize in Nepal for 30 years ranging from 1990/91 to 2019/20. Similarly, it also attempts to identify the cause of growth crops by using decomposition method. It is found that there was significant growth in area of paddy only in period I; and in production and yield in period II and overall time period. In wheat and maize, it is found that there is statistically significant increase in the area, production and yield in all the sub periods and over all time periods, except for area in wheat in period III. Similarly, it is found that in all the crops studied, greater extent of instability was observed in production, followed by the yield. And, in all the crops, area effect is higher than yield and interaction effect in all the time periods and whole study time frame. Int. J. Soc. Sc. Manage. Vol. 9, Issue-1: 13-18.